PENGARUH LEADER-MEMBER EXCHANGE TERHADAP JOB PERFORMANCE DENGAN EMPLOYEE ENGAGEMENT DAN INNOVATION BEHAVIOR SEBAGAI VARIABEL MEDIASI - Daffa Gilang Rakasiwi; Ihwan Susila; Sidiq Permono Nugroho (JURSIMA (Jurnal Sistem Informasi dan Manajemen), 2023)
The more competition between companies, companies strive to create quality resources. The success of the company in carrying out its activities is determined by human resources. The purpose of this study is to analyze the effect of leader-member exchange on job performance with employee engagement and innovation behavior as mediating variables. This research method is quantitative research. This research uses a method, namely questionnaires, research instruments in data collection. The population to be used in this study are employees of SFA Steak & Resto several outlets in Karanganyar area as many as 100 respondents. The sampling technique used in this study was to use the Saturated Sampling Technique. The data analysis technique used in this research is descriptive analysis and Structural Equation Model (SEM) analysis with Smart Partial Least Square (PLS). The results of this study are Leader Member Exchange has a significant effect on Employee Engagement. Leader Member Exchange has an insignificant effect on Job Performance. Leader Member Exchange has a significant effect on Innovation Behaviour. Employee Engagement has a significant effect on Job Performance. Innovation Behaviour has a significant effect on Job Performance. Leader-Member Exchange has an effect on Employee Engagement mediated by Employee Engagement. Leader-Member Exchange has an effect on Employee Engagement mediated by Innovation Behaviour.